Classical Islamic Malay Writing: The Contribution of Malay Ulama in the 17th Century - Mohd Puaad; Ahmad Faisal; Mohammad Irfan Farraz Haecal (Tunas Harapan Ummat Foundation, 2025)
This article discusses the involvement of Malay ulama in the production of religious books or also known as kitab kuning, especially fiqh books in the 17th century. This century, as stated by some local historians, is the beginning of the development of classical Malay books in various fields including religion. The discussion in this article is focused on two things namely the development of writing religious books, focused on fiqh books in the 17th century, while the second case reviews two sample books that have been written in the 17th century namely (1) the Sirat al-Mustaqim and (2) the Mir’ah al-Tullab fi Tashil Ma’rifah Ahkam al-Shari’ah li Mulk al-Wahhab. From the discussion of the above, it can be concluded that the activity of writing classical Malay religious works developed along with the activity of writing in other fields including the fields of Malay literature, Sufism, Malay and Islamic history, Quran and Islamic medicine